An efficient protocol for in vitro regeneration of Stevia rebaudiana - Ahmed, Sheikh Rashel; Howlader, Md Moniruzzaman Shohag; Sutradhar, Pijush; Yasmin, Sabina (Asian Journal of Medical and Biological Research, 2016)
An efficient high frequency plant regeneration protocol through direct organogenesis was developed for Sevia rebaudiana. Shoot tips containing axillary buds were used as an explant and inoculated on Murashige and Skoogs (MS) medium containing 3% (w/v) sucrose, 0.6% (w/v) agar supplemented with various concentrations of benzy-ladenine (BA), kinetin (Kn) and thidiazuron (TDZ).. BAP proved to be a better choice than Kn and the maximum number of shoots (3.75) was obtained on 2.0 mgL-1 BAP concentration. Considering all parameters, combination of BAP and Kn gave comparatively better performance than single BAP or Kn. TDZ was effective for multiple shooting. Though, 1.5 mgL-1 TDZ gave the best number of shoots (14.5), but 1.0 mgL-1 TDZ gave best performance in response to all parameters under study. The highest number of shoots was obtained in 60 mlL-1 coconut water, but 40 mlL-1 coconut water gave the best result to all parameters. Root induction was tested by using two auxins namely NAA and IBA at different concentrations (1.0, 1.5, 2.0 mgL-1) on the MS medium. IBA at 1.0 mgL-1 increased the rooting response (66.67%), number of roots (7.0) and root length (2.9 cm). Higher concentration of IBA and NAA (2.0 mgL-1) showed poor results of rooting response (33.33%). Asian J. Med. Biol. Res. March 2016, 2(1): 95-106